Evaluating land management options for transitioning to regenerative coffee systems in Kenya - Waswa, Boaz; Rahn, Eric; Ocimati, Walter; Notenbaert, An; Ogutu, Francis; Mutegi, Judy (2025)
Regenerative agricultural approaches can empower farmers to position coffee in the context of global demand and regulations relating to sustainable production, fair trade, healthy and safe diets. As Kenya advances toward regenerative coffee farming, evaluating farmers’ perceptions and preferences for sustainable land management options and their contribution to improved productivity, soil health, and climate resilience is crucial. A study was carried out under the Coffee Farmers Income Resilience Program supported by IDH, employing the Evaluating Land Management Options (ELMO) tool, a participatory technique used to assess farmers’ preferences and barriers to adopting sustainable land management practices. The study engaged 302 households across seven counties in Kenya including Bungoma, Nandi, Nyeri, Murang’a, Kirinyaga, Embu and Tharaka Nithi. The findings reveal that farmers have adopted various regenerative practices such as agroforestry, mulching, and terracing. Beyond contributing to improved productivity, these regenerative practices are preferred for their long-term environmental benefits and advantages, including improved soil health, diversified income streams, and low upfront investment. Potential challenges for farmers adopting regenerative methods include intensity of labour required, expenses incurred for implementation, long-term harvest of return, higher risks of pests, risk of losing soil quality, transport challenges, lack of yield improvement and little or no impact. Despite these challenges, farmers recognise the lasting impact of these practices. These results offer valuable insights for designing training programs, financial support, and government policies critical for transitioning coffee farmers to regenerative coffee systems. By evaluating these options, Kenya’s coffee sector can achieve long-term sustainability, maintain high-quality yields, and strengthen resilience against climate change.